Instruments of Political Control: National Oil Companies, Oil Prices, and Petroleum Subsidies. (March 2015) - Cheon, Andrew; Lackner, Maureen; Urpelainen, Johannes
Global petroleum subsidies peaked at US520 billion in the summer of 2008 and reached US212 billion in 2011, carrying high fiscal and environmental costs. Why do some countries spend so much money to subsidize petroleum consumption? Previous studies suggest that oil-rich autocracies lacking institutional capacity are the main culprits. However, they cannot explain why oil importers with capable bureaucracies, such as Argentina, Brazil, and Malaysia, subsidized petroleum products. We argue that governments in countries with national oil companies (NOCs) use petroleum subsidies to cushion the effects of increasing oil prices. Empirically, we examine the relationship between oil prices and domestic gasoline prices in 175 countries, 2002-2009. An NOC halves the effect of oil price increases on the domestic gasoline price. This effect is strongly associated with the institutional design of NOCs, as increased autonomy shields them from political interference by the government.